Syn-Eruptive Processes During the January–February 2019 Ash-Rich Emissions Cycle at Mt. Etna (Italy): Implications for Petrological Monitoring of Volcanic Ash - D’Oriano, Claudia; Del Carlo, Paola; Andronico, Daniele; Cioni, Raffaello; Gabellini, Pietro; Cristaldi, Antonio; Pompilio, Massimo (Frontiers in Earth Science, 2022)
Low-intensity emission of volcanic ash represents the most frequent eruptive activity worldwide, spanning the whole range of magma compositions, from basalts to rhyolites. The associated ash component is typically characterized by heterogeneous texture and chemical composition, leading to misinterpretation of the role of syn-eruptive processes, such as cooling and degassing during magma ascent or even magma fragmentation. Despite their low intensity, the ash emission eruptions can be continuous for enough time to create problems to health and life networks of the communities all around the volcano. The lack of geophysical and/or geochemical precursor signals makes the petrological monitoring of the emitted ash the only instrument we have to understand the leading mechanisms and their evolution. Formation of low-level plumes related to ash-rich emissions has increasingly become a common eruptive scenario at Mt. Etna (Italy). In January–February 2019, an eruptive cycle of ash-rich emissions started. The onset of this activity was preceded on 24 December 2018 by a powerful Strombolian-like eruption from a fissure opened at the base of the New Southeast Crater. A lava flow from the same fissure and an ash-rich plume, 8–9 km high a.s.l., from the crater Bocca Nuova occurred concurrently. After about 4 weeks of intra-crater strombolian-like activity and strong vent degassing at summit craters, starting from 23 January 2019, at least four episodes of ash-rich emissions were recorded, mainly issued from the Northeast Crater. The episodes were spaced in time every 4–13 days, each lasting about 3–4 days, with the most intense phases of few hours. They formed weak plumes, up to 1 km high above the crater, that were rapidly dispersed toward different directions by dominant winds and recorded up to a distance of 30 km from the vent. By combining observations on the deposits with data on textural and chemical features of the ash components, we were able to discriminate between clasts originated from different crater sources and suggest an interpretive model for syn-eruptive processes and their evolution. Data indicate the occurrence of scarce (<10 vol.%) fresh juvenile material, including at least four groups of clasts with marked differences in microlite content and number density, and matrix glasses and minerals composition. Moreover, a large amount of non-juvenile clasts has been recognized, particularly abundant at the beginning of each episode. We propose that the low amount of juvenile ash results from episodic fast ascent of small magma batches from shallow reservoirs, traveling within a slow rising magma column subjected to cooling, degassing, and crystallization. The large number of non-juvenile clasts deriving from the thick crater infill of variably sealed or thermally altered material at the top of the magma column is suggested to contribute to the ash generation. The presence of a massive, granular crater infilling accumulating in the vent area may contribute to buffer the different geophysical signals associated with the active magma fragmentation process during the low-energy ash eruptions, as already evidenced at other volcanoes.